PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN PENINGKATAN PROFESIONAL GURU TERHADAP KINERJA GURU DI MASA PANDEMI COVID-19 - Yunus Russamsi; Hanhan Hadian; Acep Nurlaeli (Perkumpulan Manajer Pendidikan Islam (PERMAPENDIS) Indonesia, 2020)
Process during the Covid-19 pandemic which was carried out at home in accordance with a government circular in order to break the chain of the spread of Covid 19.